A Psoriatic Arthritis Case with Skin Manifestations Occurring 20 Years After the Arthritis - Filiz Eser; Hatice Bodur; Ümit Seçkin; Pınar Eroğlu (Archives of Rheumatology, 2009)
Psoriatic arthritis (PsA) is an inflammatory arthritis in the spondyloarthropathy group. The variety of the clinical findings, lack of diagnostic criteria, potential conflicting syndromes, and the possibility of joint involvement before the skin involvement make the diagnosis more difficult. In 15-20% of the cases with PsA, it is reported that the lesions start after the arthritis. Here, we present a 59-year-old female patient with PsA, whose skin manifestations were diagnosed 20 years after the arthritis. She had symmetrical polyarthritis on her hand joints and had been followed up with the diagnosis of seronegative RA. (Turk J Rheumatol 2009; 24: 110-2)